Size and ownership of enterprise and innovation activities of manufacturers of food and beverages in western Poland in 2009-2012 = Wielkość i charakter własności przedsiębiorstwa a działalność innowacyjna przedsiębiorstw sektora spożywczego w zachodniej Polsce w latach 2009-2012 - Dzikowski, Piotr (Zielona Góra: Faculty of Economics and Management Press)
The paper presents the results of a study aimed at determining the nature of relations between innovation activities and company size and company?s ownership in the food and beverage sector in western Poland in 2009-2012. The most innovation active enterprises are medium-sized companies, which are also the only group which leads innovation cooperation with its suppliers and customers. Among the most frequently taken innovation activities are: the implementation of new technological processes, investments in new fixed assets including computer software and investments in R & D. The least innovation active firms are domestic micro and small enterprises.
Keywords: sektor spożywczy; działalność innowacyjna; wielkość przedsiębiorstwa; własność przedsiębiorstwa; food and beverages sector; innovation activity; company size; company?s ownership